Use of Arduino for monitoring angles on oil platforms for didactics purposes - Heleno Pontes (Universidade Estadual de Alagoas, 2023)
Offshore platforms are floating structures, located in the sea, which can carry out drilling and production activities, in some cases, storage and transfer. For the proper development of the activities of the operators, the platform must remain in balance. If there is any movement, that these movements are within tolerable limits. The movements of vessels are mainly caused by environmental actions: ocean current, wind and ocean wave. For the mapping of movements, several sensors are installed in the structures in order to obtain more accurate information, having in many cases, more than one sensor mapping the same information. In order to read this information, acquisition systems must be connected to computers so that the correct interpretation of what is being measured can be performed. The use of Arduino has grown in recent years due to the possibility of using it with sensors and the associated low cost. In this way, this work proposes the use of an Arduino system and MPU6050 (sensor with gyroscope and accelerometer) to map gyres on offshore platforms for didactic purposes. The implementation of the code for reading the information from the accelerometer and the gyroscope is carried out and it is verified that the results obtained are consistent with the movements that were imposed. It is concluded, then, the feasibility of use for mapping the turn of a platform.